Chapter Scholarly feminists - Clisby, Suzanne (Amsterdam University Press, 2023)
In this article we reflect on our longstanding work within a powerful European network of feminist scholars. Here we consider how we have collaboratively created and sustained embodied infrastructures of care in building feminist academic scholarship, supporting the next generations of feminist scholars into the academy, and working through creative praxis to generate feminist and queer activism within and beyond academic spaces. We argue that our gendered bodies, identities and material actions have built embodied infrastructures that have facilitated feminist access to higher education and career development and advanced gender equalities discourse beyond the academy through our creative activist networks.